The Baroque Era - Strunk, Oliver 1901-1980; Murata, Margaret (New York Norton, 1998)
Though traditionally labeled "Baroque," the seventeenth and early eighteenth centuries in music could as easily be termed "early modern," since many of the genres that are popular todaywere established during that time.And as music itself was becoming more and more of a public affair, discussions and writings about music increased greatly. In The Baroque Era, Margaret Murata presents twoscore readings from a constellation of personalities whose thoughts and opinions help define the period for us. We hear, of course, from the composers (Monteverdi, Schütz, Rameau, Bach) and the theorists (Artusi, Simpson, North, Mattheson), but we also find the words of nonmusicians, ranging from the famous (Joseph Addison, Lady Mary Montagu) to the unknown "Truthful Reporter."
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Music history